Programmable Assembly of Colloidal Nanoparticles Controlled by Electrostatic Potential Well. Issue 10 (11th October 2022) - Liu, Yuanlan; Wang, Yawen; Sun, Yinghui; Li, Dong; Liang, Zhiqiang; Liang, Wenkai; Gao, Heng; Qin, Wei; Qian, Hongqiang; Jiang, Lin
Abstract : Electrostatic Potential Wells In article number 2200066, Lin Jiang and co‐workers report a bowl‐shaped electrostatic potential well which can be formed based on the combined effects of a positively charged nanoparticle and a negatively charged substrate. The regulation of substrate potential changes the state of the electrostatic potential well, thus controlling the rationed capture of negatively charged nanoparticles and the programmable assembly of the colloidal nanostructures.